Development of a Surveilens System as a Means for Collection and Reporting of Infectious Diseases in Puskodono Health Center, Sragen - Sari, Kiki Puspita; Adi, Kusworo; Agushybana, Farid (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2023)
Surveillance is an important activity in the context of disease data collection. The results of these surveillance activities can also be used as a consideration for making decisions related to disease management, especially infectious diseases. The aim of the research was to develop an information system for surveillance of infectious diseases for data collection and reporting to support management decision making at the Sukodono Health Center, Sragen.This research method is qualitative and quantitative. Prototype model research development. The research population is all parties involved in the development of an Infectious Disease Management Information System at the Sukodono Health Center, Sragen. The subjects of this study were the Head of the Community Health Center, the Head of the Infectious Diseases Program and the four Communicable Diseases Program Holders. the research object is the Communicable Disease Health Center Management Information System. This research method is qualitative and quantitative. Prototype model research development. The subjects of this study were one head of the health center, one head of the infectious disease program and four holders of the infectious disease program. the research object is the Communicable Disease Health Center Management Information System. Data analysis in this study was carried out by means of content analysis for qualitative and descriptive analysis methods for quantitative. The acquisition of the evaluation results from the total average percentage is Accurate at (62.19%), Complete at (83.89%), timeliness (84.44%), and Relevant at (95.20%). Meanwhile, in terms of data accuracy (accuracy) and completeness of content or data availability (content), information system users are very satisfied, as indicated by the results of the total average percentage of both 80.36 and 99.36% indicating that the user is very confident in the completeness and correctness of the examination data that has been inputted into the information system by paramedics. The results of the evaluation of the information system as a whole are 81.43%, meaning that the Information System for Surveillance of Communicable Diseases can be received and used by users of the information system very well